Assessment of yield strength mismatch in X80 pipeline steel welds using instrumented indentation. (December 2018) - Midawi, A.R.H.; Simha, C.H.M.; Gerlich, A.P.
Abstract: Strain-based design (SBD) of pipelines allows stress owing to displacement-controlled loads originating from landslides, seismic motions, or frost heaves, to exceed yield stress. In such cases, the distribution of the strain over a large area (pipe) rather than local area (weld) is preferred. Accordingly, in SBD, yield strength of the circumferential girth weld is over matched when compared to the base metal. In this work, API-X80 pipeline steel sections were joined together using the robotic Gas-Metal Arc Welding (GMAW) process; filler metals and shielding gases were varied to achieve three different levels of strength (even, over and under match) between the weld and base metal. Weld metal and HAZ cross-section microstructures were investigated and correlated with micro-hardness maps to ensure that different mismatch levels were achieved. Yield strengths of the welds in the hoop direction were measured using both instrumented indentation and conventional tensile testing. The instrumented indentation technique used a 100- μ m diameter nearly-flat indenter to estimate yield strengths for the welds and heat-affected zones from the load-displacement response for each zone. The measured yield strengths were compared with 0.2% offset tensile yield strength obtained through conventional tensile testing of all-weld and base metal specimens. Strength measurements, in the hoop direction, for weld metal from both of the techniques agreed to within 4.6%. The results showed that the nearly-flat tip indentation method can be used as a tool to directly estimate strength mismatch of pipeline girth welds. Measurements of yield strength for narrow coarse and fine grained heat-affected zones, which cannot be measured through any other method, can also be assessed using the techniques described herein.